Comparison of etiology and outcome of dogs undergoing cardiopulmonary resuscitation with different conformation: the Shepherd versus the Bulldog - Ossman, Junes E.; Rozanski, Elizabeth A.; DeStefano, Ian M.; Mandryk, Deirdre Givens; Berlin, Noa; Hoehne, Sabrina N.; Silverstein, Deborah C.; Balakrishnan, Anusha, for Reassessment Campaign on Veterinary Resuscitation (RECOVER) CPR Registry Consortium (Frontiers in Veterinary Science, 2025)
ObjectiveTo investigate whether chest and head conformation in dogs is associated with the etiology of cardiopulmonary arrest (CPA) and likelihood to experience sustained return of spontaneous circulation (sROSC) following cardiopulmonary resuscitation (CPR).DesignRetrospective study from the years 2000 and 2023 of dogs that underwent CPR that were one of two body types: either mesocephalic (Shepherd) or brachycephalic (Bulldog).SettingElectronic medical records from one veterinary record system and from the Reassessment Campaign on Veterinary Resuscitation (RECOVER) CPR Registry were reviewed.AnimalsA total of 162 dogs were included: 72 in the mesocephalic group (MC) and 90 Bulldogs in the brachycephalic group (BC).Measurements and main resultsData recorded included signalment, body weight, disease category, whether CPA occurred during general anesthesia, suspected cause of CPA, first identified rhythm on electrocardiogram during CPA, whether defibrillation was performed, whether open chest CPR was performed, whether ROSC was achieved and if it was sustained, and survival to discharge. The BC dogs were more likely to arrest associated with respiratory disease (p < 0.001), and MC dogs were more likely to arrest associated with cavity bleeding (p = 0.012), trauma (p = 0.012), or gastric–dilatation-volvulus (p < 0.001). The MC dogs were more frequently defibrillated (p = 0.021). Return of spontaneous circulation was achieved in 34.7% (25/72) of MC dogs and 30.0% (27/90) of BC dogs (p = 0.522). Survival to discharge was similarly dismal between the two groups (p = 0.434) with 2/72 (2.8%) of MC dogs and 1/90 (1.1%) of BC dogs, which reflected both re-arrest and owner decisions. When out-of-hospital CPA cases were excluded, MC dogs were more likely to suffer from a surgical condition (p = 0.017) and experienced ventricular fibrillation more often (p = 0.032).ConclusionDogs with different head and chest confirmations developed CPA for different reasons, with diseases such as GDV and trauma more commonly affecting MC dogs and respiratory disease more commonly affecting BC dogs. Defibrillation was more common in the MC dogs.